2018
DOI: 10.1017/s0267190518000065
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Study Abroad: Stories from Ethnic Minority American Students in China

Abstract: This study focuses on the experiences of two African American and three Chinese American college students studying in China during the 2013–2014 academic year. Data were analyzed both quantitatively and qualitatively. Quantitatively, all five students made progress in their Chinese proficiency, measured by test scores, lexical diversity, and total amount of language produced in each conversation. Qualitatively, the following themes emerged: (a) interactions with Chinese people outside the classroom, (b) how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…It is likely that Terry's contact-zone socialization, growing up in a working-class, traditional Vietnamese family in an inner-city Texas neighborhood, contributed to her awareness of the intersections of multiple cultures, languages, and peoples while in Guatemala. In fact, Terry's positive sojourn experience seems in part due to the richness of her prior cross-cultural experiences (Du, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that Terry's contact-zone socialization, growing up in a working-class, traditional Vietnamese family in an inner-city Texas neighborhood, contributed to her awareness of the intersections of multiple cultures, languages, and peoples while in Guatemala. In fact, Terry's positive sojourn experience seems in part due to the richness of her prior cross-cultural experiences (Du, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has illustrated tendencies for racialized students to disengage from SA host communities due to discriminatory experiences (Goldoni, 2017; Quan, 2018; Talburt & Stewart, 1999). Students who share a linguistic, cultural, or ethnic heritage with host communities have also described being held to expectations of monolingual‐like competence, leading to linguistic insecurity and frustration (Du, 2018; Jing–Schmidt, Chen, & Zhang, 2016; Petrucci, 2007; Riegelhaupt & Carrasco, 2000). Nonetheless, students who confront discrimination based on myriad intersecting identity factors both at home and abroad potentially have much to gain from SA in regards to symbolic competence.…”
Section: Theoretical Framework and Previous Researchmentioning
confidence: 99%
“…Research has also examined the negative experiences of Asian Americans abroad, such as ethnolinguistic discrimination from locals who do not view them as Americans or who expect them to sound like a native speaker of an Asian language (Du, 2018;Van Der Meid, 2003). As a result of the COVID-19 pandemic, many countries experienced a resurgence of anti-Asian racism and even violence.…”
Section: Racial Disparities In Sa Participationmentioning
confidence: 99%
“…Nonetheless, such affinity should never be assumed, as heritage students are linguistically and culturally very diverse. In fact, heritage students may experience unique challenges while studying in their ancestral homeland, as they struggle simultaneously with not sounding authentic enough even though they may be racialized as a local (Diao, 2017;Du, 2018).…”
Section: Culturally Relevant and Critically Oriented Sa Programmingmentioning
confidence: 99%
“…As studies of Chinese BHL learners have demonstrated, they often exhibit wide variation in social interactions with locals, ethnolinguistic identities, investments, and proficiency gains during SA (Diao & Wang, 2021; Du, 2018; Jing–Schmidt et al., 2016). Some learners were highly motivated, actively participated in the local community, developed a positive attitude toward local culture and traditions, successfully renegotiated their social and racial identities, and thus gained closer ties with local people and communities as well as greater linguistic competence, forming a virtuous circle.…”
Section: Bilingual Heritage Language Learning In Study‐abroad Settingsmentioning
confidence: 99%